Holliday's engine mapping experiment revisited: a design problem with 2-level repeated measures data. (23rd February 2006) - Goldstein, Harvey; Lewis, Toby
Only a limited amount of work has been done on issues of optimum experimental design in hierarchically structured data, in spite of the importance of design efficiency. We illustrate these issues by a fresh analysis of Holliday's well-known engine mapping experiment. This experiment investigated the relation of automobile engine performance, as measured by engine torque vs. spark advance, to adjustable engine parameters or factors, viz. engine speed, load, and air/fuel ratio. We show how an optimum experiment can be designed. Our analysis suggests a general procedure of wide applicability.